Constantin von Economo´s 90th death anniversary - Teive, Hélio Afonso Ghizoni; Tensini, Fernando Spina; Lima, Plínio Garcia; Camargo, Carlos Henrique Ferreira (Arquivos de Neuro-Psiquiatria, 2021)
The year of 2021 marks 90 year since the death of the neuroscientist Constantin von Economo, whose research in various areas was extremely relevant for the field of neurology. He described lethargic epidemic encephalitis, published an atlas of the cytoarchitecture of the human cerebral cortex, and conducted multiple studies in neuroanatomy, neurophysiology, and clinical neurology. Von Economo's genius extended into other nonmedical fields such as aeronautics, and he had renowned artistic skills.
Keywords: History; Neurology; Parkinson Disease, Postencephalitic; Influenza Pandemic, 1918-1919